(untitled) (Research, Society and Development, 2021)
Objective: to reflect on the importance of an educational strategy in the process of building educational technology for guidance in assisting users undergoing coronary angiography. Content: among the various competences of Nursing, health education is shown as an effective practice in the various attributions assigned to it, in a holistic way it recognizes care within the concept of comprehensiveness, which proposes a care centered on the physical, mental, emotional, and spiritual. The main sources for this study were the relationships established between non-communicable chronic diseases, educational technology, and the dialogical-reflective process in health education. Conclusion: the health education process requires considering the interpretations or apprehensions of the context and these involve the beliefs, values, experiences, social class, religion and culture of each user. The educational intervention in assistance promotes better quality to the clientele to be assisted, offering clarifying possibilities about the exam.